Tunable quadrature sinusoidal oscillator using single-ended OTAs - Kumngern, Montree; Junnapiya, Somyot (My University, 2012)
This paper presents a new electronically tunable voltage-mode quadrature sinusoidal oscillator employing four single-ended operational transconductance amplifiers (OTAs) and two grounded capacitors. In general, the single-ended OTA configuration is simpler than the multiple-output OTA counterpart and the requirement of grounded capacitors is preferable for an integrated circuit fabrication process. Therefore, the proposed circuit provides a simple circuitry by using only single-ended OTA and highly suitable for integrated circuit (IC) implementation by using grounded capacitors. The condition of oscillation and the frequency of oscillation of the circuit can be set orthogonally. The circuit also offers an electronic control of the frequency of oscillation through adjusting the bias currents of OTAs. The theoretical results are verified by PSPICE simulators. From simulation results, it can be expressed that the proposed circuit agrees well with theory. © 2012 IEEE.
Keywords: CMOS; grounded capacitor; quadrature sinusoidal oscillator (QSO); voltage-mode circuit